منٹو کے افسانوں میں تقسیم کا پوسٹ ٹرامیٹک اسٹریس ڈس آرڈر : ( کھول دو، ٹھنڈا گوشت اور ٹوبہ ٹیک سنگھ کے تناظر میں) (Al-Aasar, 2026)
People always blame Saadat Hassan Manto having obscene writing. This article proves with evidences that Manto didn't write obscene actually Manto suffered PTSD (Post-Traumatic Stress Disorder) caused by the partition of 1947. This article highlights That Manto’s three short story’s “Khol Do”, “Thanda Gosht” and “Toba Tek Singh”, present the tragedy and pain of the psychological Laurent. In this article there are three important and necessary symbols which are the Centre. Moral injury, Emotional Numbing and Absurd Humor as Defense. In “Khol Do” Aura feels happy to our daughter alive. In “Thanda Gosht” is sexual numbness and “Toba Tek Singh” a mental disorder person partitioned the country. After reading, it is concluded that society didn’t accept Manto because he held up a mirror to the nation that clearly exposed its physical and spiritual flaws what we didn’t have the course to see. Manto’s PTSD still exists in our collective life and Hated. That’s why understanding Manto actually understands our serves and our own wounds.